APPLICATION OF THE AGILE – SCRUM METHODOLOGY TO REVAMP KPI (KEY PERFORMANCE INDEX) SYSTEM AT PT SOHO GLOBAL HEALTH - Wisnu Sukma Maulana (International Journal Science and Technology, 2023)
PT. Soho Global Health (SOHO) is a provider of health products and supplements that has 2500 employees. The overall performance of these employees is assessed on an annual KPI (Key Performance Index). Problems arise due to technology systems that were previously perceived to be very slow for processing KPI data online. New system changes that are designed with faster performance need to be done or in other words revamp the system. Substitution of a whole new system or revamp system at Soho needs to use the Agile methodology approach. Agile methodology especially the Scrum model can overcome problems that arise in the system development process, especially in the speed of processing time, many modules and complex, and also involves many teams both the development team and many elements of related users. Given that, the KPI system at SOHO processes data from thousands of employees from many divisions as a whole.